2008
DOI: 10.1021/la801968x
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Defined C60/Polymer Colloids Supramolecular Nanocomposites in Water

Abstract: We report a new supramolecular method for the synthesis of well-defined pristine C 60/polymer colloid nanocomposites in water. The colloids include polymer micelles and emulsion particles. To a polymer colloid solution in water or alcohol, we introduced C 60 solution in a solvent that is miscible with water or alcohol. After the two solutions mixed, polymer colloids and C 60 spontaneously assembled into stable colloidal nanocomposites. After a dialysis process, a nanocomposite dispersion in pure water was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Block copolymers bearing of linear and dendritic fragments in special solvents (THF/water) can aggregate in form of spherical micelles as well . For example, polymer composites were obtained by mixing a solution of the polymer colloid based on amphiphilic block copolymers (emulsions and micelles) and C 60 in toluene solution with following separation from the solution . As the result, C 60 was converted in water‐soluble colloid state and can be used in biomedical applications as photosensitizers for photodynamic cancer therapy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Block copolymers bearing of linear and dendritic fragments in special solvents (THF/water) can aggregate in form of spherical micelles as well . For example, polymer composites were obtained by mixing a solution of the polymer colloid based on amphiphilic block copolymers (emulsions and micelles) and C 60 in toluene solution with following separation from the solution . As the result, C 60 was converted in water‐soluble colloid state and can be used in biomedical applications as photosensitizers for photodynamic cancer therapy .…”
Section: Introductionmentioning
confidence: 99%
“…On mixing of micellar solutions of PS/poly‐ N , N ‐dimethylaminoethyl methacrylate (PS‐PDMAEMA) amphiphilic block copolymers with a toluene solution of fullerene, the latter interacts with a micellar particle resulting in self‐assembly of the fullerene into clusters of different sizes . Moreover, polymers containing electron‐donor atoms (oxygen, nitrogen) are able to associate in charge‐transfer complexes with the fullerene .…”
Section: Introductionmentioning
confidence: 99%
“…4 The colloidal dispersions of C 60 in the polymer micelles and/or emulsion particles prepared from the supramolecular self-assembly of amphiphilic block copolymers were also reported. 5,6 Chemical modifications of C 60 molecules by attaching polymer chains were attempted to improve the solubility. 7,8 Encapsulated particles consisting of an organic or inorganic functional material and a polymer can make advanced applications with better control of optical properties, charge carrier mobility, surface chemistry, stability, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that fullerene clusters in aqueous solution can generate singlet oxygen under photo irradiation which has implications in the studies of biomedical and environmental science 5, 6. Therefore, it is highly interesting to understand fullerene assembly behavior in the presence of polymers because controlling the clustering nanoscale morphologies of fullerene in polymer systems is of paramount importance 1–4, 7–9. Block copolymers are useful building blocks for functional nanostructured materials and it is possible to control the micro‐ and nanoscale structures by tailoring of polymer blocks and architect 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most convenient ways to organize fullerene and derivatives into nanostructures is by using the charge transfer complexation between fullerene and block copolymers. Recently, for example, interesting results on polymer solar cells were attempted using a blend of a fullerene derivative and a block copolymer of poly(3‐hexylthiophene) and poly(4‐vinylpyridine) (P3HT ‐b‐ P4VP),8 and also, well‐defined fullerene nanoclusters were formed in aqueous solutions via a block copolymer assisted self‐organization 9. However, most of the reported works focused mainly on post mortem study on the final morphology and there is no discussion on kinetics in these interesting systems.…”
Section: Introductionmentioning
confidence: 99%